An Updated Version of the Treatment Effectiveness Assessment (TEA) [Letter] - Ling W; Farabee D; Nadipelli VR; Perrochet B (Dove Medical Press, 2020)
Walter Ling,1 David Farabee,2,3 Vijay R Nadipelli,4 Brian Perrochet3 On behalf of the TEA Development Group1Department of Family Medicine, Center for Behavioral and Addiction Medicine, David Geffen School of Medicine, UCLA, Los Angeles, CA, USA; 2Department of Population Health, New York University School of Medicine, New York, NY, USA; 3Department of Psychiatry and Biobehavioral Sciences Semel Institute, David Geffen School of Medicine, UCLA, Los Angeles, CA, USA; 4Global Health Economics and Outcome Research, Indivior Inc., Richmond, VA, USACorrespondence: Walter Ling Tel +1 310 993 8111Email lwalter@ucla.edu The authors are pleased to provide this updated version of the TEA to the community of clinicians and researchers using the TEA. Previous to its original publication in 2012,1 the TEA had been used for five years by clinicians in office-based and hospital-based treatment settings, as well as by researchers in pilot projects. The TEA’s utility and psychometrics were recently studied in a large clinical trial of  extended-release  buprenorphine for opioid use disorder, demonstrating moderate to strong reliability and validity.3 The TEA has been widely adopted by researchers and clinicians in the United States and around the world. It has been translated into Spanish, Chinese, Lithuanian, and Arabic, and is being used in Europe, Asia, the Americas, and the Middle-East.View the original paper by Ling and colleagues